2019
DOI: 10.1038/s41598-019-48008-4
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated brain activity during error processing and punishment anticipation in procrastination – a monetary Go/No-go fMRI study

Abstract: Procrastination is a self-regulatory failure in which people voluntarily but irrationally delay important tasks. Trait procrastination is estimated to affect 15–20% of the total population and leads to a significant decrease in performance, satisfaction with achievements, and quality of life. Procrastination is related to impulsivity and reduced executive control, especially in the domain of inhibition. Moreover, procrastinatory tendencies seem to increase with negative affect, suggesting impaired emotion regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 70 publications
12
28
1
1
Order By: Relevance
“…Our own findings from two monetary Go/No-Go studies confirmed that procrastinators are characterized by increased impulsivity and executive dysfunctions 24,25 . In these studies, participants completed the Go/No-Go task in the standard version where subjects' gratification did not rely on task performance.…”
Section: (Adhd)supporting
confidence: 67%
See 2 more Smart Citations
“…Our own findings from two monetary Go/No-Go studies confirmed that procrastinators are characterized by increased impulsivity and executive dysfunctions 24,25 . In these studies, participants completed the Go/No-Go task in the standard version where subjects' gratification did not rely on task performance.…”
Section: (Adhd)supporting
confidence: 67%
“…This deficit was, however, only observed in punishment condition but not in reward and standard conditions suggesting that procrastinators' executive deficits are particularly strong when punishment is expected. The second study 25 confirmed the impairment in executive control in procrastinators in the punishment condition. In this functional brain imaging (fMRI) study, we found reduced activations in procrastinators during the whole punishment condition in anterior cingulate cortex (ACC) and right dorsolateral prefrontal cortex (dlPFC), regions that are related to self-control 29 .…”
Section: (Adhd)supporting
confidence: 52%
See 1 more Smart Citation
“…Indeed, abstinent cocaine-dependent participants showed hypoactivity of the ACC and right DLPFC in relation to punished errors in the Go/No-go task (Hester et al, 2013). We have found similar results (diminished ACC and right DLPFC activity during punishment condition in the Go/No-go task) in individuals high in procrastination (Wypych et al, 2019). These findings are in line with prior theories (Heatherton & Wagner, 2011) and suggest that impairment of prefrontal control by punishment threat or negative emotions may operate for many subject groups characterized by low SR (note however that previously mentioned study (Duehlmeyer & Hester, 2019) showed higher DLPFC activity in tobacco-smoking individuals during re-encoding of later-corrected errors, possibly reflecting higher difficulty and/or effort needed to correctly perform in the task).…”
Section: Possible Mechanismssupporting
confidence: 77%
“…Interestingly, however, in people with alcohol dependence, increased ERN was found, possibly in relation to higher anxiety (Schellekens et al, 2010). Diminished error-related brain activity has also been found in people with criminal recidivism (Aharoni et al, 2013), procrastination (Wypych et al, 2019;Michałowski et al, submitted), and high impulsivity (Ruchsow et al, 2005). These results suggest impaired error processing may link transdiagnostically to multiple groups with low SR.…”
Section: Error Processingmentioning
confidence: 93%